The Role of Return on Assets, Current Ratio, Debt to Equity Ratio and Dividend Payout Ratio on Stock Prices of Manufacturing Companies on the Indonesia Stock Exchange for the 2020-2023 Period - Arifin, Arifin (Journal of Information Systems and Management (JISMA), 2024)
Financial ratio is one of the important indicators used by a company or institution to assess business performance through financial data. In addition to measuring the health of a company's finances, financial ratios are often used as a reference in making decisions and evaluating existing performance. In addition, financial ratios are also one of the important data that are taken into account by both investors and potential investors. The purpose of this study is to test the effect of return on assets, current ratio, debt to equity ratio, and dividend payout ratio on stock prices. The sample in this study were companies included in the LQ45 Index on the Indonesia Stock Exchange for the period 2020 - 2023. The sampling technique in this study used the purposive sampling method, where there were 18 companies included in the LQ45 Index that met the predetermined criteria. This study uses a multiple linear regression analysis method using the Statistical Package for the Social Science (SPSS) version 19.0 and Microsoft Excel to test the effect between independent variables on dependent variables. The results of this hypothesis test indicate that the current ratio and debt to equity ratio have an effect on stock prices, while return on assets and dividend payout ratio do not affect stock prices. It is expected that the results of this study can be used as a consideration for companies listed on the Indonesia Stock Exchange, especially those included in the LQ45 Index, to continue to develop and pay attention to factors that can affect Stock Prices such as Current Ratio and Debt to Equity Ratio. Companies are also expected to continue to pay attention to the Return On Assets and Dividend Payout Ratio values, because in this study they do not affect Stock Prices. For investors, the results of this study are expected to be a consideration for choosing a company in making short-term or long-term investments by looking at the company's prospects as seen from factors that affect Stock Prices such as Debt to Equity Ratio and Dividend Payout Ratio.